The Bantú-African Concepcion of Death - Musyoka, Gregory Nzau (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The question of death remains a great concern for mankind since the very beginning. The Bantu-African conception of death and the after-life has its own contribution in giving answers to this mysterious happening. It is very interesting to see how this attempt coincides or differs with others.